Memahami Pembangunan Ekonomi Provinsi Nusa Tenggara Timur Berbasis Energi Baru dan Terbarukan - Adrianus Amheka (TATALOKA, 2020)
The economy as an indicator of the development of the Province of East Nusa Tenggara (NTT) becomes important to understand its relationship with activity level of the industrial sector in supporting the economic wheel. This study objectives are to determine the current development optimization to project economic improvement in the province of NTT by utilizing the local potential of renewable energy (RE) in order to support the Indonesian National Energy Policy (INEP) through implementation of the Long-range Energy Alternative Planning (LEAP) system for the period 2015 to 2030 with existing industrial sub-sectors in the province with integrated of operating systems and energy systems assessments. The results show that the largest primary energy use is the food and beverage industry, while the largest secondary energy consumption is from the cement industry, due to government efforts to boost large-scale industries. The mix of electric energy sourced from RE showed a drastic increase up to 2030, which amounted to 19.05% compared to other types of energy while achieving the INEP target, namely the utilization of RE as much as possible and minimizing oil use, then optimizing gas use. Thus, the economy of NTT Province is currently still adequate to optimize the use and utilization of long-term RE.